The Impact of Psoriasis on Quality of Life – Exploring the Interplay Between Pain, Depression, and Stress - Smereka, Szymon; Jabłoński, Wiktor; Chmielecka, Urszula; Wolińska, Natalia; Riccardi, Caterina; Frycz, Jan (Dermatology Review/Przegląd Dermatologiczny, 2025)
Psoriasis is a chronic, immune-mediated inflammatory disorder that has a significant negative impact on patients’ quality of life. In addition to the physical manifestations of cutaneous lesions and potential joint involvement, psoriasis is associated with substantial psychosocial burdens, including elevated rates of pain, depression, and stress. The main goal of this paper is to examine the impact of psoriasis on quality of life, focusing on the role of chronic pain, psychological stress and depression. It has been proven that many patients who suffer from psoriasis experience pain, mostly neuropathic, which can significantly worsen their daily activities and has a negative impact on mental health. Depression, a common co-disease amongst psoriatic patients, is strongly related with visible symptoms of psoriasis, such as lesions and also underlying inflammatory mechanisms. Depression can affect up to 62% of patients. In addition to that, stress can enhance the intensity of symptoms, creating a vicious cycle which further worsens both psychological and physical well-being. Anti-inflammatory treatments, in particular those that target cytokine pathways, have been shown to be effective in alleviating both physical and psychological symptoms. This study highlights the necessity for integrated strategies that address both physical and mental health for the effective management of psoriasis.